1999
DOI: 10.1063/1.123461
|View full text |Cite
|
Sign up to set email alerts
|

Valence-band structure of wurtzite GaN including the spin-orbit interaction

Abstract: Optical absorption in semiconductor quantum dots coupling to dispersive phonons of infinite modes J. Appl. Phys. 112, 074324 (2012) Electronic structures of single-layer boron pnictides Appl. Phys. Lett. 101, 153109 (2012) The direct and indirect bandgaps of unstrained SixGe1−x−ySny and their photonic device applications J. Appl. Phys. 112, 073106 (2012) Structural, elastic, and polarization parameters and band structures of wurtzite ZnO and MgO J. Appl. Phys. 112, 073503 (2012) Full-zone k.p model for the ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
73
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(78 citation statements)
references
References 23 publications
(13 reference statements)
5
73
0
Order By: Relevance
“…In much previous work the parameter A 7 has been assumed to be zero, but recently it has been shown that its inclusion can give an improved description of the valence bands. 26 The parameter A 7 can be evaluated using the formula…”
Section: K"p Model For the Wurtzite Structurementioning
confidence: 99%
“…In much previous work the parameter A 7 has been assumed to be zero, but recently it has been shown that its inclusion can give an improved description of the valence bands. 26 The parameter A 7 can be evaluated using the formula…”
Section: K"p Model For the Wurtzite Structurementioning
confidence: 99%
“…In unstrained wurtzite GaN, there are three closely spaced top valence bands (VBs) at the Brillouin-zone center, usually referred to as heavy-hole (HH), light-hole (LH) and crystal-field split-off hole (SCH) [46,47]. These valence band states have atomic p-orbital character in contrast to the bottom conduction band (CB), which has atomic ^-orbital character.…”
Section: B Conduction and Valence Band Changes In The Presence Of Stmentioning
confidence: 99%
“…40,41 These VB states have atomic p-orbital character, in contrast to the bottom conduction band ͑CB͒, which has atomic s-orbital character. Since the large band gap of GaN reduces the interaction of CB and VB states, the Hamiltonian for the strain dependence of the VB can be separately given by the 6 ϫ 6 matrix 3…”
Section: B Conduction and Valence Band Changes In The Presence Of Stmentioning
confidence: 99%